Human Resource Management and Corporate Culture in Small Enterprises: Case of Ukraine - Petrova, I.L.; Albdrane, M.; Петрова, Ірина Леонідівна (ФОП Лібуркіна Л. М., 2020)
The article deals with the peculiarities of human resources management system in small enterprises in Ukraine, identifies its distinctive features, which reflect in organizational culture and provide unique opportunities of productivity growth in an organization, and on the other hand impede its development. Human resources management system is considered as a complex and multifaceted process, covering the set of organizational practices and activities aimed at effi cient and effective utilization of the most valuable resource of an organization – people and at the same time as a dynamic system which should be constantly improved. The specificity of human resource management in small businesses in Ukraine was analyzed and compared with European experience. The authors’ attention was paid to fore key characteristics of human resources management system in small business as staff professional development, using outsourcing and leasing of staff, motivation system as well as improvement of corporate culture. These characteristics show both controversial problems of small enterprises growth and opportunities of their further development. Besides, weakness of Ukrainian small business is evident in limited HR-practices, informal procedures and relations, lack of social protection, uncertainty and unpredictability of doing business, insufficient level of corporate culture. Relying on the results of research suggestions on improvement of human resources management system in small enterprises were made.
Keywords: human resources management; small business; development of staff; motivation; outsourcing; leasing of staff; corporate culture